Las Normas Internacionales de Información Financiera. Una revisión teórica del proceso en Latinoamérica - Yábar, Ben Yusef (2018)
The world is undergoing a process of integration in all fields, economic, social, environmental, cultural, among others, that make economic agents adapt their practices and converge correctly to the new scenario. Part of that process has to do with the implementation of accounting harmonization policies whose objective is for companies to be able to provide their users with transparent and representative accounting information of the economic and financial reality of the various sectors in a country. Therefore, the present article, theoretically reviews the origins of this process, describing the role of international organizations to achieve standardization in information, in addition, some antecedents are commented on previous research and finally details the origins of the process in Different countries in Latin America. This theoretical review uses the document review technique, which analyzes previous research and legal basis of various Latin American countries to describe the process of implementation of the International Financial Reporting Standards in the region. Finally, it is determined that there are two main causes of the slow progress in the implementation of such regulations in the region: lack of knowledge in accounting professionals, low technology and a high cost in the implementation of the regulations.